2020
DOI: 10.3389/fpubh.2020.562882
|View full text |Cite
|
Sign up to set email alerts
|

At the Epicenter of COVID-19–the Tragic Failure of the Global Supply Chain for Medical Supplies

Abstract: The tragic failure of the global supply chain in the face of the current coronavirus outbreak has caused acute shortages of essential frontline medical devices and personal protective equipment, crushing fear among frontline health workers and causing fundamental concerns about the sustainability of the health system. Much more coordination, integration, and management of global supply chains will be needed to mitigate the impact of the pandemics. This article describes the pressing need to revisit the governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 30 publications
(36 reference statements)
0
102
0
Order By: Relevance
“…Extended exposure to large numbers of infected patients places them at direct risk of contracting the infection. This is exacerbated by the lack of personal protective equipment (PPE), which has been a subject of major concern across the world ( 18 , 19 ). Reports of an increasing number of healthcare worker deaths due to COVID-19 have created a sense of fear and outrage ( 20 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extended exposure to large numbers of infected patients places them at direct risk of contracting the infection. This is exacerbated by the lack of personal protective equipment (PPE), which has been a subject of major concern across the world ( 18 , 19 ). Reports of an increasing number of healthcare worker deaths due to COVID-19 have created a sense of fear and outrage ( 20 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Workers have also reported anxiety about transmitting the infection to their families, elderly parents and young children (23,24). There is a critical need for increased efforts to provide adequate PPE (18).…”
Section: Impact Of Covid-19 On Healthcare Workersmentioning
confidence: 99%
“…Telemedicine has been applied in the field of Pediatric Surgery [ 15 ] and pediatrics for a long time as well [ 16 , 17 ] and was already on a trajectory of exponential global growth [ 18 ]. The COVID-19 pandemic has boosted the utilization of telemedicine greatly [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) recommends healthcare providers wear NIOSH-approved N95 or equivalent or higherlevel respirators/masks while treating patients with suspected or confirmed SARS-CoV-2 infection 20 . However, due to the sudden rise in demand, low initial supplies on hand, panic buying by the population and healthcare centers, decreased supply from suppliers, and a lack of an effective distribution plan by the federal government to maintain domestic inventory, many healthcare practices found themselves lacking nearly all forms of PPE [21][22] . These issues with U.S. supply chains of PPE have been known when similar, albeit less profound, shortages occurred following the 2009 H1N1 influenza pandemic and the 2014 Ebola virus pandemic 23 , and a world-wide survey done in April of 2020 revealed that over 50% of healthcare providers caring for COVID-19 patients lacked at least one piece of normal PPE and more than 30% were recycling facemasks 24 .…”
Section: Article In Pressmentioning
confidence: 99%